Glob·ali·zaʹ·tion n. the irrational fear that someone in China will take your job - Greenwald, Bruce C., 1946- (John Wiley & Sons, 2009)
Most supporters and opponents of globalization accept as true certain key ideas that govern the terms of the debate. Globalization, they contend, is the single dominant force shaping the world's economies both today and into the future; an irresistible and growing part of economic reality. They see the fates of business, labor, and entire nations all determined by their ability to adapt to its dictates. These and other similar notions have become so completely accepted that they are now embraced as the conventional wisdom. In this book, the authors argue that these ideas are either largely fal.